Redemption for the Museum of the Bible? Artifacts, provenance, the display of Dead Sea Scrolls, and bias in the contact zone. (4th May 2021) - Kersel, Morag M.
ABSTRACT: How is it possible in this moment of museum decolonization, critical examination of museum ethics and practice, calls for repatriations and reparations, and restorative justice, that a brand new museum is embroiled in controversy over the acquisition, study, and display of archaeological artifacts? Museum aversion to addressing complex issues of provenance, documentation, fakes, and archaeological site destruction caused by looting results in distorted displays and inaccurate interpretations of the material record and injustice and bias in the contact zone ( sensu Bennett, Boast, Clifford, and Pratt). The exhibition of archaeological artifacts from the 'Holy Land', specifically the Dead Sea Scrolls on display at the Museum of the Bible, offers a compelling case study. The Dead Sea Scrolls as contact zone (writ small) allow for the consideration of curatorial decision-making, visitor engagement, honesty, untold stories, and the potential for redemption at the Museum of the Bible.